SEPARATION AND IDENTIFICATION OF FORCED DEGRADATION PRODUCTS OF LOFEXIDINE BY USING LC-MS/MS - SK, MASTANAMMA; ANJALI T, SATYA; J, TEJASWI; M, CHIRANMAI; LATHA K, HEMA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: A rapid and reliable isocratic LC-MS/MS method was developed and validated for the separation and identification of stress degradation products (DPs) of lofexidine. Methods: Lofexidine, a non-opioid centrally acting alpha2-adrenergic receptor agonist, was subjected to hydrolysis (acidic, alkaline, and neutral), oxidation, photolysis, and thermal stress as per International Council on Harmonization specified conditions. The drug showed extensive degradation under alkaline, acidic, oxidation, and photolytic stress condition. Results: A total of 14 DPs were observed and the chromatographic separation of the drug and its DPs were achieved on waters symmetry C18 (150 × 4.6 mm, 3.5 μm) column using water and acetonitrile (75:25 v/v) as mobile phase. The DPs were separated and identified using LC-MS/MS. The LC-MS/MS method was validated with respect to specificity, linearity, accuracy, and precision. Conclusion: The proposed method was used for impurity profiling and routine quality control tests of lofixidine.